Handbook of Trait Narcissism Key Advances, Research Methods, and Controversies (Springer International Publishing, 2018)
This unique reference surveys current theoretical and empirical advances in understanding individual differences in narcissistic personality, as well as the latest perspectives on controversies in the field. Wide-ranging expert coverage examines the many manifestations of narcissism, including grandiose, vulnerable, communal, and collective varieties. Narcissism's etiology, the role of social media culture in its maintenance and amplification, and the complex phenomena of narcissistic leadership, spirituality, friendship, and love are just a snapshot of topics that are examined. The book's section on intrapersonal processes delves into how the narcissistic mind works, as well as how narcissists feel about themselves and their peers. It also investigates narcissists' grasp of emotions. Chapters explore associated personality traits and numerous other important correlates of narcissistic personality. New approaches to research, assessment methods, and opportunities for intervention-both immediate and long-term, are discussed throughout. In addition, trait narcissism is examined in an even-handed manner that incorporates state-of-the-art research into antecedents and consequences (both good and bad) of narcissistic personality. Among the topics in the Handbook: What separates narcissism from self-esteem? A social-cognitive perspective. The many measures of grandiose narcissism. Parents' socialization of narcissism in children. What do narcissists know about themselves? Exploring the bright spots and blind spots of narcissists' self-knowledge. Understanding and mitigating narcissists' low empathy. Interpersonal functioning of narcissistic individuals and implications for treatment engagement. Offering nuanced analysis of a particularly timely subject, The Handbook of Trait Narcissism is fascinating and informative reading for psychologists and psychology students, as well as scholars in anthropology, sociology, economics, political scientists, and more. .